Is the incidence of motor neuron disease higher in French military personnel?. Issue 1 (2nd January 2020) - Vlaar, Tim; Elbaz, Alexis; Moisan, Frédéric
Abstract: Objective: Previous studies, mostly from the United States, showed an increased risk of motor neuron disease (MND) in military personnel. We compared MND incidence rates in French military personnel to that in the general population. Methods: Among persons covered between 2010 and 2016 by the Caisse Nationale Militaire de Sécurité Sociale (CNMSS, military personnel) and the Caisse Nationale d'Assurance Maladie des Travailleurs Salariés (CNAMTS, general population) aged ≥50 years, we identified incident MND cases and estimated populations at risk using national health insurance databases. We estimated relative risks (RRs) and 95% confidence intervals (CIs) separately for men and women using age-adjusted Poisson regression. Analyses were also stratified by 10-year age groups. We used the E-value approach and probabilistic bias analysis to assess robustness of the results regarding unmeasured confounding by smoking. Results: On average, 25 cases/year were newly diagnosed with MND among military personnel aged ≥50 years. The incidence rate was higher for male military personnel compared to the general population (RR = 1.16; 95% CI = 1.05–1.29) but was similar for women (RR = 1.02; 95% CI = 0.79–1.31). Although there were no significant interactions with age and sex, the association was mainly explained by men aged 70–79 years. The prevalence of ever-smoking should be at least 1.1-fold higher in male CNMSS compared to male CNAMTS members to make the association in male military personnel not significant. Conclusion: MND incidence was 16% higher in French male military personnel, in agreement with studies from other countries. Smoking may contribute to this finding. Further studies are needed to identify exposures that drive this association.